Effect of subdivision and contraction of edges on the dimension of a graph - Gervacio, Severino V. (Animo Repository, 1998)
Dr. Severino Gervacio, Mathematics faculty and holder of the Brother John C. Lynam, FSC Professorial Chair delivered the lecture on Effect of Subdivision and Contraction of Edges on the Dimension of a Graph. The lecture was also part of the Mission Statement-University week celebration.